Toward a Tailored Model of Youth Justice: A Qualitative Analysis of the Factors Associated with Successful Placement in a Community-Integrated Facility - Souverein, Fleur (International journal of offender therapy and comparative criminology, 2022)
Community-integrated facilities provide security and care for justice-involved youth, minimizing risks, while allowing youth to build on protective factors within their community. Literature on the specific factors that determine appropriate placement in a community-integrated facility, versus a more restrictive high-security setting, is scarce. Current screening and assessment tools for youth are mostly applied after placement and mainly focus on the reoffending risk. The current paper explored which youth, who would previously have been placed in a high-security setting, could be successfully placed in a less secure community-integrated facility. Through qualitative analysis, based on the perspectives of professionals, youth and parents, the current paper identified six distinct domains to guide appropriate screening and outlines guidelines for policy and practice. These domains include: motivation to comply, short and long-term perspective, current offense context, crime history, safety and support from youth’s network, and mental health and intellectual abilities.